The impact of fixed prosthodontic education kit on patients' awareness and knowledge in Universiti Teknologi MARA (UiTM) / Nik Rahayyu Nik Zulkifeli ... [et al.] - Nik Zulkifeli, Nik Rahayyu; Nik Mahmood, Nik Zarina; Rosli, Nur Nabila; Mohd, Siti Hajar (2019)
The study aims to develop Fixed Prosthodontic Education Kit(FPEK) to measure patients' awareness and knowledge on fixed prosthodontic treatment options. The patients' knowledge in advantages and disadvantages of each type of prosthesis was also evaluated. Methods. The study was divided into 2 parts: 1) Development of the kit, 2) Modification, validation and questionnaire distribution to patients. The kit comprises of various types of bridge and crown in a rectangular box, flashcards and a video. In Part 2, a quantitative study using a modified and validated self-administered questionnaire from previous studies. It was randomly distributed to 343 participants who later were divided into 2 groups; Group 1, assisted with Fixed Prosthodontic Education Kit(FPEK) and verbal-assisted Group 2. The participants were invited to answer a 5-points likert scale, nine items questionnaire with awareness and knowledge domains. Data was recorded in SPSS version 25. An independent t-test was used for statistical analysis with p <0.05. Result: No significant difference was found on the awareness of the fixed prosthodontics among the groups prior to the introduction of the kit.Patient's also has higher knowledge in advantages and disadvantages of each type of prosthesis when analyzed using Independent t-test (p=0.00). Conclusion: A Fixed Prosthodontic Education Kit is a useful education tool to provide knowledge and create awareness to patients. It facilitates dental practitioners and provides higher impact in giving information before a decision-making of the treatment prescribed.